Disease severity and blood cytokine concentrations in dogs with natural Babesia rossi infection. (20th May 2019) - Leisewitz, Andrew; Goddard, Amelia; De Gier, Jill; Van Engelshoven, Jessica; Clift, Sarah; Thompson, Peter; Schoeman, Johan P.
Abstract: Aims: Babesia rossi causes severe disease in dogs. Here, we describe the association between serum cytokine concentrations and disease severity. Methods: Seventeen controls and 55 PCR confirmed B rossi ‐infected dogs were included. Diseased dogs were subdivided into 23 critically ill and 32 relatively well cases. Serum concentrations of 11 cytokines and biochemical markers of disease severity were determined. Results: Significant differences were detected for IL‐6, IL‐8, IL‐10, MCP‐1 and TNF‐α between the groups. Generally, the more complicated the disease, the more pro‐inflammatory the cytokine milieu. IL‐8 showed a reverse trend and was negatively correlated with disease severity. IL‐6, MCP‐1 and TNF‐α were also significantly higher in the dogs that died (n = 9) compared to the dogs that survived (n = 46). IL‐8 showed the opposite. MCP‐1 and TNF‐α were negatively correlated with biochemical markers of severity. Glucose was negatively correlated with IL‐6. Cortisol, peripheral parasite density and band neutrophil count were positively correlated, whilst thyroid hormone was negatively correlated with IL‐6, MCP‐1 and TNF‐α. Conclusions: As in malaria and sepsis, B rossi infection induces a pro‐inflammatory cytokine storm that correlates with disease severity and adverse outcome. The multiplicity of cytokines involved argues for redundancy in the system once the disease is established.